Reimagining Judge Oversight: Duties and Functions of the Judicial Commission in Action - Anita Kadir; Ahmad Sabirin; Syaqila Binte Suzaini (University of Jember, Indonesia, 2026)
In recent years, public confidence in the Indonesian judiciary has continued to decline due to repeated cases involving judicial corruption, abuse of authority, and violations of the judicial code of ethics. This condition highlights the need for a stronger and more independent supervisory mechanism capable of ensuring accountability, transparency, and integrity within the judicial system. This paper examines the urgency of judicial supervision reform in Indonesia through strengthening the duties and functions of the Supreme Court as an external supervisory institution for judicial power. The rise of ethical violations, allegations of bribery, and independent behaviour by some judges threatens the principles of the rule of law and the supremacy of the constitution. This research uses a normative juridical method. The findings show that the authority of the Supreme Court, which is limited to the recommendatory function, without the right to impose direct sanctions or conduct investigations into alleged criminal acts by judges, causes institutional disharmony, legal uncertainty, and a low level of implementation of the Supreme Court's recommendations. The design of the authority of the Supreme Court in the current positive legal framework is not adequate to answer the demands of judicial reform and the restoration of public trust. The proposal includes expanding the authority of the Constitutional Court to impose administrative sanctions directly, including the possibility of dismissing judges in cases of serious ethical violations, as well as granting limited investigative authority for violations related to the code of ethics and the integrity of judges. This strengthening is important to avoid the dominance of the Supreme Court's internal supervision, which has the potential to give birth to judicial tyranny, as well as to affirm the position of the Supreme Court as an effective auxiliary organ in ensuring the accountability, independence, and professionalism of judges in the Indonesian judicial system.